C.) 1600 pi cm3
When you do 10^2 you get 100 and you multiply that by the height so 16 and you get 1600.
4(x+2)+2=14
4x+8+2=14
4x+10=14
Subtract 10 from both sides
4x=4
Divide by 4 on both sides
x=1
It looks like the differential equation is
![\left(x^2y + e^x\right) \,\mathrm dx - x^2\,\mathrm dy = 0](https://tex.z-dn.net/?f=%20%5Cleft%28x%5E2y%20%2B%20e%5Ex%5Cright%29%20%5C%2C%5Cmathrm%20dx%20-%20x%5E2%5C%2C%5Cmathrm%20dy%20%3D%200)
Check for exactness:
![\dfrac{\partial\left(x^2y+e^x\right)}{\partial y} = x^2 \\\\ \dfrac{\partial\left(-x^2\right)}{\partial x} = -2x](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%5Cleft%28x%5E2y%2Be%5Ex%5Cright%29%7D%7B%5Cpartial%20y%7D%20%3D%20x%5E2%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cpartial%5Cleft%28-x%5E2%5Cright%29%7D%7B%5Cpartial%20x%7D%20%3D%20-2x)
As is, the DE is not exact, so let's try to find an integrating factor <em>µ(x, y)</em> such that
![\mu\left(x^2y + e^x\right) \,\mathrm dx - \mu x^2\,\mathrm dy = 0](https://tex.z-dn.net/?f=%20%5Cmu%5Cleft%28x%5E2y%20%2B%20e%5Ex%5Cright%29%20%5C%2C%5Cmathrm%20dx%20-%20%5Cmu%20x%5E2%5C%2C%5Cmathrm%20dy%20%3D%200)
*is* exact. If this modified DE is exact, then
![\dfrac{\partial\left(\mu\left(x^2y+e^x\right)\right)}{\partial y} = \dfrac{\partial\left(-\mu x^2\right)}{\partial x}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%5Cleft%28%5Cmu%5Cleft%28x%5E2y%2Be%5Ex%5Cright%29%5Cright%29%7D%7B%5Cpartial%20y%7D%20%3D%20%5Cdfrac%7B%5Cpartial%5Cleft%28-%5Cmu%20x%5E2%5Cright%29%7D%7B%5Cpartial%20x%7D)
We have
![\dfrac{\partial\left(\mu\left(x^2y+e^x\right)\right)}{\partial y} = \left(x^2y+e^x\right)\dfrac{\partial\mu}{\partial y} + x^2\mu \\\\ \dfrac{\partial\left(-\mu x^2\right)}{\partial x} = -x^2\dfrac{\partial\mu}{\partial x} - 2x\mu \\\\ \implies \left(x^2y+e^x\right)\dfrac{\partial\mu}{\partial y} + x^2\mu = -x^2\dfrac{\partial\mu}{\partial x} - 2x\mu](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%5Cleft%28%5Cmu%5Cleft%28x%5E2y%2Be%5Ex%5Cright%29%5Cright%29%7D%7B%5Cpartial%20y%7D%20%3D%20%5Cleft%28x%5E2y%2Be%5Ex%5Cright%29%5Cdfrac%7B%5Cpartial%5Cmu%7D%7B%5Cpartial%20y%7D%20%2B%20x%5E2%5Cmu%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cpartial%5Cleft%28-%5Cmu%20x%5E2%5Cright%29%7D%7B%5Cpartial%20x%7D%20%3D%20-x%5E2%5Cdfrac%7B%5Cpartial%5Cmu%7D%7B%5Cpartial%20x%7D%20-%202x%5Cmu%20%5C%5C%5C%5C%20%5Cimplies%20%5Cleft%28x%5E2y%2Be%5Ex%5Cright%29%5Cdfrac%7B%5Cpartial%5Cmu%7D%7B%5Cpartial%20y%7D%20%2B%20x%5E2%5Cmu%20%3D%20-x%5E2%5Cdfrac%7B%5Cpartial%5Cmu%7D%7B%5Cpartial%20x%7D%20-%202x%5Cmu)
Notice that if we let <em>µ(x, y)</em> = <em>µ(x)</em> be independent of <em>y</em>, then <em>∂µ/∂y</em> = 0 and we can solve for <em>µ</em> :
![x^2\mu = -x^2\dfrac{\mathrm d\mu}{\mathrm dx} - 2x\mu \\\\ (x^2+2x)\mu = -x^2\dfrac{\mathrm d\mu}{\mathrm dx} \\\\ \dfrac{\mathrm d\mu}{\mu} = -\dfrac{x^2+2x}{x^2}\,\mathrm dx \\\\ \dfrac{\mathrm d\mu}{\mu} = \left(-1-\dfrac2x\right)\,\mathrm dx \\\\ \implies \ln|\mu| = -x - 2\ln|x| \\\\ \implies \mu = e^{-x-2\ln|x|} = \dfrac{e^{-x}}{x^2}](https://tex.z-dn.net/?f=x%5E2%5Cmu%20%3D%20-x%5E2%5Cdfrac%7B%5Cmathrm%20d%5Cmu%7D%7B%5Cmathrm%20dx%7D%20-%202x%5Cmu%20%5C%5C%5C%5C%20%28x%5E2%2B2x%29%5Cmu%20%3D%20-x%5E2%5Cdfrac%7B%5Cmathrm%20d%5Cmu%7D%7B%5Cmathrm%20dx%7D%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cmathrm%20d%5Cmu%7D%7B%5Cmu%7D%20%3D%20-%5Cdfrac%7Bx%5E2%2B2x%7D%7Bx%5E2%7D%5C%2C%5Cmathrm%20dx%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cmathrm%20d%5Cmu%7D%7B%5Cmu%7D%20%3D%20%5Cleft%28-1-%5Cdfrac2x%5Cright%29%5C%2C%5Cmathrm%20dx%20%5C%5C%5C%5C%20%5Cimplies%20%5Cln%7C%5Cmu%7C%20%3D%20-x%20-%202%5Cln%7Cx%7C%20%5C%5C%5C%5C%20%5Cimplies%20%5Cmu%20%3D%20e%5E%7B-x-2%5Cln%7Cx%7C%7D%20%3D%20%5Cdfrac%7Be%5E%7B-x%7D%7D%7Bx%5E2%7D)
The modified DE,
![\left(e^{-x}y + \dfrac1{x^2}\right) \,\mathrm dx - e^{-x}\,\mathrm dy = 0](https://tex.z-dn.net/?f=%5Cleft%28e%5E%7B-x%7Dy%20%2B%20%5Cdfrac1%7Bx%5E2%7D%5Cright%29%20%5C%2C%5Cmathrm%20dx%20-%20e%5E%7B-x%7D%5C%2C%5Cmathrm%20dy%20%3D%200)
is now exact:
![\dfrac{\partial\left(e^{-x}y+\frac1{x^2}\right)}{\partial y} = e^{-x} \\\\ \dfrac{\partial\left(-e^{-x}\right)}{\partial x} = e^{-x}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%5Cleft%28e%5E%7B-x%7Dy%2B%5Cfrac1%7Bx%5E2%7D%5Cright%29%7D%7B%5Cpartial%20y%7D%20%3D%20e%5E%7B-x%7D%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cpartial%5Cleft%28-e%5E%7B-x%7D%5Cright%29%7D%7B%5Cpartial%20x%7D%20%3D%20e%5E%7B-x%7D)
So we look for a solution of the form <em>F(x, y)</em> = <em>C</em>. This solution is such that
![\dfrac{\partial F}{\partial x} = e^{-x}y + \dfrac1{x^2} \\\\ \dfrac{\partial F}{\partial y} = e^{-x}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20F%7D%7B%5Cpartial%20x%7D%20%3D%20e%5E%7B-x%7Dy%20%2B%20%5Cdfrac1%7Bx%5E2%7D%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cpartial%20F%7D%7B%5Cpartial%20y%7D%20%3D%20e%5E%7B-x%7D)
Integrate both sides of the first condition with respect to <em>x</em> :
![F(x,y) = -e^{-x}y - \dfrac1x + g(y)](https://tex.z-dn.net/?f=F%28x%2Cy%29%20%3D%20-e%5E%7B-x%7Dy%20-%20%5Cdfrac1x%20%2B%20g%28y%29)
Differentiate both sides of this with respect to <em>y</em> :
![\dfrac{\partial F}{\partial y} = -e^{-x}+\dfrac{\mathrm dg}{\mathrm dy} = e^{-x} \\\\ \implies \dfrac{\mathrm dg}{\mathrm dy} = 0 \implies g(y) = C](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20F%7D%7B%5Cpartial%20y%7D%20%3D%20-e%5E%7B-x%7D%2B%5Cdfrac%7B%5Cmathrm%20dg%7D%7B%5Cmathrm%20dy%7D%20%3D%20e%5E%7B-x%7D%20%5C%5C%5C%5C%20%5Cimplies%20%5Cdfrac%7B%5Cmathrm%20dg%7D%7B%5Cmathrm%20dy%7D%20%3D%200%20%5Cimplies%20g%28y%29%20%3D%20C)
Then the general solution to the DE is
![F(x,y) = \boxed{-e^{-x}y-\dfrac1x = C}](https://tex.z-dn.net/?f=F%28x%2Cy%29%20%3D%20%5Cboxed%7B-e%5E%7B-x%7Dy-%5Cdfrac1x%20%3D%20C%7D)
The answer is 4/7 in simplest form
Answer:
A. -8
B. -8
C. 20
Step-by-step explanation: